2018
DOI: 10.1016/j.geoderma.2017.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multi-day rainfall events on surface roughness and physical crusting of very fine soils

Abstract: Soil surface roughness (SSR), a description of the micro-relief of soils, affects the surface storage capacity of soils, influences the threshold flow for wind and water erosion and determines interactions and feedback processes between the terrestrial and atmospheric systems at a range of scales. Rainfall is an important determinant of SSR as it can cause the dislocation, reorientation and packing of soil particles and may result in the formation of physical soil crusts which can, in turn, affect the roughnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 79 publications
4
49
0
Order By: Relevance
“…Consistent with previous studies that reported decreased infiltration rates due to the formation of a physical crust (Bullard et al, ; Eze et al, ), the increased duration of surface ponding, especially in BaS Box #2, also suggests crust formation and associated reduced infiltration. Because the vegetation cover protected the underlying soil from raindrop impacts, hindering infiltration, the post‐storm ponding duration observed in VC Box #2 was significantly lower than observed in BaS Box #2.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with previous studies that reported decreased infiltration rates due to the formation of a physical crust (Bullard et al, ; Eze et al, ), the increased duration of surface ponding, especially in BaS Box #2, also suggests crust formation and associated reduced infiltration. Because the vegetation cover protected the underlying soil from raindrop impacts, hindering infiltration, the post‐storm ponding duration observed in VC Box #2 was significantly lower than observed in BaS Box #2.…”
Section: Discussionsupporting
confidence: 90%
“…The successive rainfall events increased PR in all surface treatment boxes, an observation reported by others (Bullard et al, ; Feng et al, ; Nciizah & Wakindiki, ; Neave & Rayburg, ), suggesting that surface crusts developed and progressed due to the raindrop impact‐induced processes. The rate of crust development was influenced by the area of the surface that was directly exposed to raindrop impact (e.g., that was not protected by canopy); the crust became stronger and continued to develop in the BaS boxes.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…With the beginning of precipitation, a slight increase in the number of particles was recorded first, and then, a slow but steady decline. As stated above, the slight increase in the number of particles may be caused by resuspension (Pruppacher et al, ; Wang et al, ; Josserand and Thoroddsen, ; Bullard et al, ). The peaks in the number of particles occurred when the rain almost completely reduced its intensity.…”
Section: Resultsmentioning
confidence: 98%